Improved in vitro Efficacy of Baloxavir Marboxil Against Influenza A Virus Infection by Combination Treatment With the MEK Inhibitor ATR-002 - Hamza, Hazem; Shehata, Mahmoud M.; Mostafa, Ahmed; Pleschka, Stephan; Planz, Oliver (Frontiers in Microbiology, 2021)
Currently, all available antiviral drugs against influenza virus (IV) that target the virus proteins directly, like Baloxavir acid (BXA), lead to viral resistance. Therefore, cellular mechanisms and factors essential for IV replication are promising antiviral targets. As IV strongly depends on the virus-induced Raf/MEK/ERK signal pathway for efficient generation of infectious progeny virions, this pathway represents an important target. We aimed to determine whether the MEK inhibitor ATR-002 (PD0184264) is able to impair replication of BXA-resistant influenza A viruses (IAV) and whether a treatment combining BXA and ATR-002 improves the therapeutic efficiency in vitro. A549 Cells infected with different IAV strains including BXA-resistant variants were treated with ATR-002 or BXA and the effect on virus titer reduction was determined. The synergistic effect of ATR-002 and BXA was also analyzed using different evaluation methods. The data demonstrated that ATR-002 has a significant and dose-dependent inhibitory effect on IAV replication across different strains and subtypes. IAV with the PA-I38T mutation shows resistance against BXA, but are still susceptible towards ATR-002. The combination of ATR-002 and BXA exhibited a synergistic potency reflected by low combination index values. In conclusion we show that ATR-002 permits to counteract the limitations of BXA against BXA-resistant IAV. Moreover, the results support the use of ATR-002 (i) in a mono-therapy, as well as (ii) in a combined approach together with BXA. These findings might also apply to the treatment of infections with IAV, resistant against other direct-acting antiviral compounds.